1988
DOI: 10.1007/bf00254189
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of cisplatin on i. v. L-PAM plasma pharmacokinetics in ovarian cancer patients

Abstract: Melphalan (L-PAM) pharmacokinetics were investigated in nine ovarian cancer patients before and after cisplatin (DDP) treatment. When L-PAM was given 24 h before DDP, the elimination half-life (t 1/2 beta), plasma clearance (Clp), and volume of distribution (Vd beta) of L-PAM were, respectively: 46.4 +/- 6.7 min, 20.5 +/- 3.7 l/m2, and 306.8 +/- 34.4 ml/min per square meter. When L-PAM was inoculated 24 h after DDP, t 1/2 beta, Clp, and Vd beta were 47.5 +/- 6.3 min, 20.4 +/- 2.8 l/m2, and 322.0 +/- 54.1 ml/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The drug concentrations defined in our experiments are in agreement with those achieved in humans: the ID70 range found for tallimustine against myeloid progenitors (90-235 ng ml-') is in the range (104-189 ng ml') of those reported in four patients 1 h after administration of doses near the MTD (Sessa et al, 1994). A similar trend was also seen for carzelesin (in vitro 1.7-6.3 ng ml-', in humans 1-2 ng ml-') (Wolff et al, 1996) and L-PAM (in vitro 590-2100 ng ml-', in humans 100-800 ng ml-' at a dose below the MTD) (Zucchetti et al, 1988). A similar in vivo-in vitro correlation for myelotoxicity between concentrations active on clonogenic tests and plasma concentrations achieved in phase I studies was found with other compounds such as pyrazolacridine (Parchment et al, 1994;Rowinsky et al, 1995).…”
Section: Discussionsupporting
confidence: 71%
“…The drug concentrations defined in our experiments are in agreement with those achieved in humans: the ID70 range found for tallimustine against myeloid progenitors (90-235 ng ml-') is in the range (104-189 ng ml') of those reported in four patients 1 h after administration of doses near the MTD (Sessa et al, 1994). A similar trend was also seen for carzelesin (in vitro 1.7-6.3 ng ml-', in humans 1-2 ng ml-') (Wolff et al, 1996) and L-PAM (in vitro 590-2100 ng ml-', in humans 100-800 ng ml-' at a dose below the MTD) (Zucchetti et al, 1988). A similar in vivo-in vitro correlation for myelotoxicity between concentrations active on clonogenic tests and plasma concentrations achieved in phase I studies was found with other compounds such as pyrazolacridine (Parchment et al, 1994;Rowinsky et al, 1995).…”
Section: Discussionsupporting
confidence: 71%